Pemberdayaan Kesehatan Lansia Melalui Program LIBAS Hipertensi Sebagai Upaya Menangani Masalah Hipertensi pada Lansia di Desa Mertak Tombok - Reza Indra Wiguna; Lalu Jupriadi; Dita Retno Pratiwi; Lia Arian Apriani; Lidya Wardani; Mar'aten Solehah; Ninin Wulandari; Riadatul Hartati; Ahmad Mustiadi; Ema Jihan Fazira (Sekolah Tinggi Ilmu Kesehatan Baiturrahim Jambi, 2022)
Hypertension is a non-communicable disease that is one of the world's premature deaths. WHO (World Health Organization) estimates that currently the global prevalence of hypertension is 22% of the total world population. Southeast Asia is in the 3rd position with a prevalence of 25% of the total population. According to the NTB Provincial Health Office in 2019, out of all districts/cities in NTB, people with hypertension were over 18 years old, i.e. more women than men. Based on the data above, we are interested in proposing an idea of health services for the elderly group with hypertension through the LIBAS Hipertensi (Lansia Bebas Hipertensi) program. LIBAS is one of the health innovation programs as an effort to promote health in the elderly group in controlling hypertension. The Hypertension Libas activity aims to improve the ability of the elderly to control and treat hypertension. The method used is by conducting counseling and demonstrations targeting the elderly group in Mertak Umbak Hamlet and Jempong Eler Hamlet, amounted to 20 respondents., Hypertension Libas activities are carried out during 14 the day accompanied by elderly health cadres. The counseling activities carried out in the Libas Hypertension program were in the form of education about the problem of hypertension in the elderly, then the elderly were taught to process rosella tea as a therapy to reduce high blood pressure. The results of the Hypertension LIBAS activities can increase the knowledge of the elderly about hypertension and increase the ability of the elderly to control blood pressure by consuming rosella tea.